2016
DOI: 10.1002/adfm.201503673
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nanostructure and Coating on the Mechanics of Carbon Nanotube Arrays

Abstract: Nanoscale materials are one of the few engineering materials that can be grown from the bottom up in a controlled manner. Here, the effects of nanostructure and nanoscale conformal coating on the mechanical behavior of vertically aligned carbon nanotube (CNT) arrays through experiments and simulation are systematically investigated. A modeling approach is developed and used to quantify the compressive strength and modulus of the CNT array under large deformation. The model accounts for the porous nanostructure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 39 publications
2
14
0
Order By: Relevance
“…Figure S4 (Supporting Information) shows the compressive failure of some micropins, probably occurred during the closure and clamping of the top mold. The compressive failure mechanism observed in our 15 nm coated a‐SiC micropins has been extensively studied by others …”
mentioning
confidence: 68%
See 1 more Smart Citation
“…Figure S4 (Supporting Information) shows the compressive failure of some micropins, probably occurred during the closure and clamping of the top mold. The compressive failure mechanism observed in our 15 nm coated a‐SiC micropins has been extensively studied by others …”
mentioning
confidence: 68%
“…The tailoring of the CNT‐based nanostructure performance strongly depends on the achieved porosity, the coating material and its infiltration within the nanotube network. Recently, Poelma et al have shown how the mechanical response of high aspect ratio foam‐like VA‐CNTs can be tuned from foam‐like toward brittle ceramic by simply varying the thickness of an amorphous silicon carbide coating . No study has yet been published regarding the thermal conductivity enhancement consequent to the infiltration of a conformal coating within a porous VA‐CNT array.…”
mentioning
confidence: 99%
“…Ceramics are commonly used as conformal coating for vertically aligned CNT arrays to improve compressive strength and stiffness. [19,20] The porous nature of the densified CNT films also allows researchers to use methods such as atomic layer deposition (ALD) to weld the nanostructures of CNTs by uniform inter-tubes deposition of Al 2 O 3 thin films. [21] In this study we report on a detailed TEM investigation of these nanostructures in the CNT films.…”
Section: Mechanical Properties Measurementmentioning
confidence: 99%
“…Based upon the principles of continuum mechanics, the strain experienced by the RVE due to the compressive stresses would emulate the deformation occuring at the macroscale. Hence, the mean deflection of the network can be calculated by assuming the CNT segment as a beam with as shown below [34], (6) where for MWCNT (7) where is the Young's modulus of the CNT, is the moment of inertia of CNT and di is the inner diameter of MWCNT.…”
Section: Compression Deformation Of Bpmentioning
confidence: 99%
“…CNTs are usually synthesized in the form of vertically aligned [1] or random networks of fibers [2][3][4][5]. Aligned networks of CNTs have been found to be valuable in numerous applications but there are experimental challenges involved in the preparation [5,6]. It is significantly easier to prepare buckypaper (BP), which is a self-supporting random network of CNTs entangled together by means of weak van der Waals interactions at tube-tube junctions.…”
Section: Introductionmentioning
confidence: 99%